Exploring gut microbiota in adult Atlantic salmon (Salmo salar L.): Associations with gut health and dietary prebiotics - Jie Wang; Yanxian Li; Alexander Jaramillo-Torres; Olai Einen; Jan Vidar Jakobsen; Åshild Krogdahl; Trond M. Kortner (Animal Microbiome, 2023)
Abstract Background The importance of the gut microbiota for physiological processes in mammals is well established, but the knowledge of their functional roles in fish is still limited. The aims of this study were to investigate associations between variation in taxonomical composition of the gut microbiota and gut health status in Atlantic salmon and to explore possible modulatory effects of dietary prebiotics in one net-pen farm in open water. The fish with initial mean body weight of around 240 g were fed diets based on the same basal composition, either without (Ref diet) or with (Test diet) yeast cell wall based-prebiotics, during the marine production phase from December to September the following year. Sampling was conducted at three sampling time points: January, April, and September, with average water temperature of 3.9 ℃, 3.4 ℃ and 9.6 ℃, respectively. Results As the fish progressed towards September, growth, brush border membrane enzyme activities, and the expression in the gut of most of the observed genes involved in immune (e.g., il8, cd4a, myd88, il1b, gilt, tgfb, cd8b and cd3), barrier (e.g., zo1, occludin, ecad, claudin25b and claudin15), and metabolism increased significantly. Lipid accumulation in pyloric enterocytes decreased remarkably, suggesting improvement of gut health condition. The growth of the fish did not differ between dietary treatments. Further, dietary prebiotics affected the gut health only marginally regardless of duration of administration. Regarding gut microbiota composition, a decrease in alpha diversity (Observed species, Pielou and Shannon) over time was observed, which was significantly associated with an increase in the relative abundance of genus Mycoplasma and decrease in 32 different taxa in genus level including lactic acid bacteria (LAB), such as Lactobacillus, Leuconostoc, and Lactococcus. This indicates that developmental stage of Atlantic salmon is a determinant for microbial composition. Multivariate association analysis revealed that the relative abundance of Mycoplasma was positively correlated with gut barrier gene expression, negatively correlated with plasma glucose levels, and that its relative abundance slightly increased by exposure to prebiotics. Furthermore, certain LAB (e.g., Leuconostoc), belonging to the core microbiota, showed a negative development with time, and significant associations with plasma nutrients levels (e.g., triglyceride and cholesterol) and gene expression related to gut immune and barrier function. Conclusions As Atlantic salmon grew older under large-scale, commercial farm settings, the Mycoplasma became more prominent with a concomitant decline in LAB. Mycoplasma abundance correlated positively with time and gut barrier genes, while LAB abundance negatively correlated to time. Dietary prebiotics affected gut health status only marginally.